Pathways to change in existential group treatment: experiences from older adults with psychological distress in primary care - Isak Erling; Carl Anton Waltersson; Margda Waern; Maria Tillfors; Sara Hed; Stefan Wiktorsson; Anne Ingeborg Berg (BMC Geriatrics)
Abstract Background There is a need for age-adapted treatments for older adults with psychological distress and existential therapy could be of particular relevance for mental health issues related to aging. The aim of this study was to understand the process of existential therapy for older adults by exploring how pathways to change are expressed in experiences from existential group treatment. Methods Seventeen participants aged 75 and above with psychological distress took part in individual interviews after completion of a 7-week existential group treatment in primary care. The participants were recruited from five primary care centers in the Västra Götaland Region of Sweden. Data were analyzed using thematic analysis in relation to pathways to change in Wampold’s Contextual Model of Psychotherapy. Results The analysis resulted in six themes. Central themes in understanding pathways to change in existential group treatment for older adults were Dare to talk about life and death, Letting myself be old, and Making the most of life despite difficulties. When recognizing things as they are and being able to face the reality of being old without avoidance, a wish to make the most of life despite difficulties emerged. Perspectives on the therapeutic process also included Commitment matters, Engaging with others and Developing new and different relationships. These themes captured the participants’ experiences of choosing to commit to treatment and the relational process of engaging in existential group treatment. Conclusions Older adults’ experiences of existential group treatment suggest that engaging in existential dimensions of aging can be helpful when done in a structured setting together with others. Reduced experiential avoidance, increased determination to do what feels meaningful, relational aspects as well as one’s own commitment to therapy can help explain how existential group treatment may contribute to change among older adults with psychological distress.